2009
DOI: 10.1016/j.yfrne.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein phosphatases and mitochondria in the neuroprotective effects of estrogens

Abstract: In the present treatise, we provide evidence that the neuroprotective and mito-protective effects of estrogens are inexorably linked and involve the ability of estrogens to maintain mitochondrial function during neurotoxic stress. This is achieved by the induction of nuclear and mitochondrial gene expression, the maintenance of protein phosphatases levels in a manner that likely involves modulation of the phosphorylation state of signaling kinases and mitochondrial pro- and anti-apoptotic proteins, and the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 217 publications
(260 reference statements)
1
32
0
Order By: Relevance
“…Similar to our data from the cortex, Valles et al [20] found that Aβ induced upregulation of the p38MAPK pathway, whereas this activation was prevented by E2 pretreatment. In addition, E2 was shown to induce phosphatases to exert a neuroprotective effect in vitro [79]. Therefore, under these conditions, E2 was able to reverse the proposed Aβ-induced kinase overactivation in the SSCTX (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our data from the cortex, Valles et al [20] found that Aβ induced upregulation of the p38MAPK pathway, whereas this activation was prevented by E2 pretreatment. In addition, E2 was shown to induce phosphatases to exert a neuroprotective effect in vitro [79]. Therefore, under these conditions, E2 was able to reverse the proposed Aβ-induced kinase overactivation in the SSCTX (fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, classical ERs may act as transcriptional partners at non-ERE sites, such as AP-1 sites, interacting with other DNA-binding elements [17]. Membrane/cytoplasm-initiated ER signaling involves the interaction of classical ERs in the membrane or the cytoplasm with G-proteins, glutamate receptors, signaling kinases and phosphatases [18][19][20][21] as well as actions on the mitochondria [21]. Finally, estradiol may signal through ER-dependent mechanisms by non-classical ERs, such as those mediated by G-protein-coupledreceptor 30 (GPR30), a putative membrane ER [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective effects of 17␤-estradiol (E2) have been clearly documented for more than a decade (25)(26)(27)(28) in a variety of disease states involving mitochondrial disruption, but the exact mechanism of action is currently poorly understood (20,29,30). Estrogen has been demonstrated to have antioxidant properties (31)(32)(33)(34)(35); modulate Ca 2ϩ flux (36); stabilize mitochondrial membrane potential (20,34,35); maintain the activity of electron transport chain complexes I, III, and IV; help to maintain aerobic ATP production (34,37); and promote a favorable balance of antiapoptotic-proapoptotic proteins in the cell (20,30).…”
mentioning
confidence: 99%
“…Estrogen has been demonstrated to have antioxidant properties (31)(32)(33)(34)(35); modulate Ca 2ϩ flux (36); stabilize mitochondrial membrane potential (20,34,35); maintain the activity of electron transport chain complexes I, III, and IV; help to maintain aerobic ATP production (34,37); and promote a favorable balance of antiapoptotic-proapoptotic proteins in the cell (20,30). Although the neuroprotective effects of estrogens have never been tested in an FRDA model and FRDA shows no gender bias in incidence (21,22), epidemiological studies of FRDA have shown a better prognosis in female patients (2), and the proposed mitochondrial-support mechanisms of E2 suggests a possible role for E2 in the prevention and treatment of FRDA symptoms (38).…”
mentioning
confidence: 99%